A study on the effectiveness of awareness program of workshop mechanics adopted by MJL Bangladesh Limited: a field marketing practice - Rabbani, Md. Masum (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.